Synthesis, Characterization And In Vitro Potency Of Di-, Tri-, And Tetra-Substituted Stilbene Derivatives As Vasorelaxant - Chan, Sock Ying (2021)
Vasorelaxant is the common drug used for the treatment of hypertensive emergencies. The most widely studied stilbenoid, namely resveratrol (RV) was reported its ability to induce vasorelaxation through numerous signalling pathways on the blood vessel membrane. In this study, the tri-ethoxy (SB 1a-7a), tetra-methoxy (SB 8a-13a) and di-methoxy (SB 14-16) stilbene derivatives were successfully synthesized via the conventional Wittig reaction wherein the A- and B- rings of the stilbene backbone were formed from the synthesized phosphonium salts and commercially available substituted benzaldehydes, respectively. The trans- (E) isomers were isolated and purified. The hydroxylated stilbenes (SB 1b, SB 3b-4b, SB 6b-8b and SB 11b-13b) were further synthesized from the alkoxylated stilbenes via poly O-dealkylation approach employing the modified aluminium trichloride/N,N-dimethylaniline system. All the synthesized SB compounds were elucidated by the FT-IR, 1D and 2D NMR spectroscopies. The in vitro vascular response of the synthesized SB compounds was primarily assessed on the phenylephrine (PE)-precontracted endothelium-intact isolated aortic rings of the male Sprague Dawley (SD) rats. SB 6b presented remarkable Rmax (95.11 ± 2.87 %) which was more than two-fold improvement of the vasorelaxation of the lead compound, RV (Rmax = 42.90 ± 1.67 %), suggesting the potency of SB 6b to be adopted as a new lead compound for drug optimization. The overall data illustrated the type, number and position of the substituents on the A- and B-rings were equally essential in triggering the vasorelaxation response.